The Greatness of ordinary life biography and teachings of Msgr. Josemaria Escriva (1902-1975). (Aletheia Foundation and Distributed Processing Systems, 2002)
The greatness of ordinary life multimedia CD-ROm on the life and teachings of Blessed Josemaria Escriva, priest and founder of Opus Dei.